Discretionary reductions in warrant exercise prices - Howe, J (Journal of Financial Economics, 2001)
Managers can decide to reduce a warrant's exercise price. A reduction in exercise price can induce exercise (a conversion-forcing reduction) or not (a long-term reduction). Conversion-forcing firms show an abnormal return of −1.53% on the announcement day but they perform well over the three years following the announcement. This finding suggests that the funds raised from warrant exercise are invested in profitable projects. Long-term reductions show an abnormal return of −1.15% on the announcement day. These firms also perform well following the reduction, which suggests that the lower exercise price restores managerial incentives.